1988
DOI: 10.1177/014107688808100906
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Replacement Therapy: Twice Or Thrice Daily?

Abstract: Although glucocorticoid replacement is conventionally administered twice daily, the pharmacokinetics of hydrocortisone would predict very low levels of plasma cortisol by mid-afternoon. This study compared plasma cortisol day profiles in 7 hypoadrenal patients while on twice daily and thrice daily hydrocortisone replacement. The twice daily regimen was associated with very low levels of cortisol at 16.00 and 18.00 h. This was eliminated by administering the same total dose in a thrice daily regimen. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 7 publications
2
58
0
Order By: Relevance
“…The treatment response in QoL-AGHDA score did not differ between patients receiving HC (K3.56 (95% CI K4.12 to K3.00)) and CA (K4.05 (95% CI K4.87 to K3.23); PZ0. 22).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The treatment response in QoL-AGHDA score did not differ between patients receiving HC (K3.56 (95% CI K4.12 to K3.00)) and CA (K4.05 (95% CI K4.87 to K3.23); PZ0. 22).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Whether poor quality of life is caused by nonphysiological replacement of glucocorticoids is unknown, but published data for patients on conventional replacement therapy is that morning fatigue is a particular feature: well being is lowest just before the first dose of morning glucocorticoid, rising to a maximum at lunch time, and then falling gradually towards the evening, with HRQOL better on thrice rather than twice-daily HC (13). Similarly, a twice-daily regimen of HC appears to be better than once daily (28).…”
Section: Glucocorticoid Replacement and Glucose Homeostasismentioning
confidence: 99%
“…Some clinicians favour use of prednisolone or dexamethasone, with doses based on equipotent anti-inflammatory effect (11), but doses that have an equipotent effect on the cardiovascular system are not fully established. Moreover, monitoring treatment remains a challenge, and is based on clinical assessment and biochemical parameters (12)(13)(14). Recently, efforts have focused on the development of newer formulations of HC to provide circadian glucocorticoid replacement therapy aimed to imitate more closely the normal physiological cortisol rhythm (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found little differences between standard replacement regimens and their effects on subjective health and quality of life (5,6,7,8,9); however, many of these studies were cross-sectional (7,8,9). Other studies investigated less physiological HC regimes, suggesting an advantage of imitating the circadian rhythm of cortisol secretion (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, differences in timing of the doses were not studied. The remaining studies assessed only patients with primary AI (2, 10, 11) or did not differentiate between patients with primary AI and SAI (5). Hence, the aim of this study was to analyze the effects of three glucocorticoid replacement regimens commonly administered in SAI patients on a broad range of psychological outcome parameters.…”
Section: Introductionmentioning
confidence: 99%